Urgensi Manajemen Pemasaran Perguruan Tinggi Islam (Studi Kasus UIN Raden Mas Said Surakarta di Era Society 5.0) - Sri Haryanti; Giyoto; Yusuf Rohmadi; M. Alfan Haidar Dhofir (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2023)
This paper discusses the urgency of marketing management for higher education institutions, as it plays a crucial role in determining the sustainability of enrollment and increasing public trust in the university. The university's marketing management is carried out by taking into account the constantly changing consumers or stakeholders. Market research, positioning, and building the university's reputation are conducted in such a way that the relevance and accuracy of the strategies are always appropriate. The university's vision, mission, programs, and strengths cannot be recognized without promotion through good marketing management. This paper uses a qualitative method with data collection techniques through interviews, observations, and documentation. The results of this study show that UIN Raden Mas Said Surakarta has implemented marketing management to increase enrollment sustainability with new innovations according to the demands of society 5.0. Furthermore, UIN has also utilized social media platforms such as Facebook, Instagram, YouTube, Twitter, website, alumni network, and others as marketing tools.